Spektrum Gerakan Perlindungan Pegunungan Meratus: Sejarah, Visi, dan Dinamika Gerakan Sosial Masyarakat Adat Dayak Pitap - Salam, Ismail Abdi; Hamid, Ismar; Baihakki, Fajar (Prodi Sosiologi FISIP ULM, 2025)
The agrarian conflict involving the Pitap Dayak indigenous community represents a form of resistance against the expansion of extractive corporations that threaten the sustainability of their customary lands and cultural identity. This study aims to explore the underlying factors driving the community’s defense of their territory and to describe the characteristics of their social movement in the context of agrarian conflict. Employing a qualitative case study approach, data were gathered through participatory observation, in-depth interviews, and documentation, then analyzed using the Manual Data Analysis Procedure (MDAP). The findings reveal that the Pitap Dayak community has successfully harmonized traditional values, such as collective solidarity, customary spirituality, and community deliberation, with modern strategies, including legal advocacy, youth leadership development, and the use of digital technology. The involvement of NGOs further enhances the movement, positioning it within the framework of new social movements that are deliberative, adaptive, and well-networked. This study demonstrates that the effectiveness of indigenous movements is not solely determined by structural constraints, but by the community’s capacity to construct collective meaning, maintain cohesion, and adapt strategically to socio-political and economic pressures. Academically, the research contributes to studies on indigenous customary law, agrarian conflict, and environmental sociology. Practically, it offers valuable insights into the resilience of indigenous communities in defending ancestral land rights and ecological stewardship. Future research is encouraged to further investigate the role of digital tools and cross-sector alliances in reinforcing the sustainability and legitimacy of indigenous movements.